DOP26 COVID-19 vaccine effectiveness in Inflammatory Bowel Disease patients on tumor-necrosis factor inhibitors: Real world data from a mass-vaccination campaign. (21st January 2022) - Lev Zion, R; Focht, G; Lujan, R; Mendelovici, A; Friss, C; Greenfeld, S; Kariv, R; Ben-Tov, A; Matz, E; Nevo, D; Barak-Corren, Y; Dotan, I; et al.
Abstract: Background: Some studies have shown decreased serological response to vaccination in patients on anti-tumor necrosis factor (TNF) medications. While the large majority of these patients do seroconvert after vaccination, titers have generally been lower and one study showed reduced neutralizing and inhibitory functions. One real-world population-based study compared found no increased infection rate in anti-TNF treated patients, but infection rates were low. The low event rate mandates exploration in longer-term population-based data. We used the epi-Israeli IBD Research Nucleus (IIRN) database to explore the effectiveness of COVID-19 vaccination in IBD patients in Israel. Methods: We included all IBD patients insured in two of the four Israeli HMOs, covering 35% of the population, by validated algorithms, and selected those who received two doses of Pfizer BNT162b2 vaccine. These were matched by date of vaccination ±3 days and demographic variables to non-IBD controls. The primary outcome was incidence of positive COVID-19 PCR following vaccination between December, 2020 to June, 2021. Results: 12, 640 IBD patients received two vaccine doses; the matched cohort included 4, 946 matched pairs (total 9, 892 subjects). Mean age was 50.5±16.1 years and median follow-up was 22 weeks (range 4.1–24.4). Fifteen (0.3%) vaccinated IBD patients tested positive compared with 15 (0.3%) vaccinated non-IBD controls (OR=1 [95%CI 0.49–2.05], p=1.0). Patients on anti-TNF and/or corticosteroids did not have a higher incidence of positivity – neither compared to the entire group nor to IBD patients treated with vedolizumab/ustekinumab, even after precise matching for demographics, underlying diseases and IBD severity. Conclusion: In a large population-based cohort of IBD patients in Israel, vaccine effectiveness was equivalent to non-IBD controls and was not influenced by treatment with anti-TNF or corticosteroids. Notwithstanding previous findings of impaired serological response in anti-TNF treated IBD patients, this real-world large-scale study shows that vaccine protection is robust in IBD patients, including those on immunosuppressive medications.